Caries Experience and Salivary Parameters among Overweight Children and Adolescents - Michele B. Diniz; Ana Lídia Ciamponi; Renata Gorjão; Maria Teresa B.R. Santos; Renata O. Guaré (MDPI AG, 2013)
Obesity is a chronic disease characterized by excess body fat, which can lead to other health problems, including insulin resistance, non-alcoholic fatty liver disease, polycystic ovary syndrome, hypertension, dyslipidemia, sleep apnea, asthma, heart attack, stroke, atherosclerosis and metabolic syndrome. Currently, obesity and dental caries are major public health concerns and dietary habits are a very important common component of their etiological factors, showing some correlation with the sociodemographic characteristics of individuals presenting these diseases. In relation to caries experience, the literature suggests a correlation between obesity and dental caries in children and adolescents, in primary and/or permanent dentition, though divergent results exist regarding assessment based on the method recommended by the WHO (1997), i.e., restricted to carious lesions with cavitation. Some studies indicate greater prevalence of proximal carious lesions in obese adolescents compared with those with normal weight. Salivary changes, such as the concentrations of phosphate, sialic acid, proteins and immunoglobulins and in peroxidase activity could explain the increased probability of obese children presenting greater risk of dental caries. Thus, it is important to consider the contribution of salivary parameters in caries experience of overweight children and adolescents and the implementation of preventive measures in this population.